Sockets, shellcode, porting & coding : reverse engineering exploits and tool coding for security professionals - Foster, James C.; Price, Mike (Mike Morgan) (Syngress Pub., 2005)
Covers in detail the five most important disciplines for security professionals and software developers: coding, sockets, shellocode, porting applications, and coding security tools.